Research Trends in Mobile Learning: A Systematic Literature Review From 2011-2021 - Aisyah, Siti; Afrizal, Afrizal (Journal of Educational Technology and Instruction, 2022)
As of late, coordinating innovation into schooling keeps on standing out alongside the fast development of information and communication technology. In the writing survey, mobile learning is a learning idea that underscores the learning system with cell phones without relying upon the actual area of learning. This review means to give an exhaustive perspective on the past writing and some potential headings for scientists and instructors for additional mobile learning research. A sum of 45 papers was chosen from the ERIC database. Utilization of the term mobile learning in the title, research strategies, number of authors, major contributing nations, most useful diaries, and cell phones utilized in portable learning are investigated. The outcomes show that exploration of mobile learning has kept on getting consideration from specialists somewhat recently. Among the distributions explored, every one of the 40 articles contained the term mobile learning in the title and dynamic. As of recently, quantitative techniques are more regularly taken on in mobile learning research than quantitative strategies, blended techniques, and research and development (RnD) strategies. When arranged by country, Turkey has the most elevated commitment contrasted with different nations in this field, followed by Indonesia, South Africa, Malaysia, Thailand, China, and Spain. The greater part of the papers distributed in mobile learning research has four authors. In light of the number of articles distributed in mobile learning, Canadian Center of Science and Education, South African Journal of Education, and International Journal of Education and Development utilizing information and communication turned into the most useful diaries in this exploration. The most generally involved cellular phones in this review are cellular phones and tablets